1996
DOI: 10.1073/pnas.93.2.956
|View full text |Cite
|
Sign up to set email alerts
|

Protection of nonobese diabetic mice from diabetes by intranasal or subcutaneous administration of insulin peptide B-(9-23).

Abstract: The observation that overt type I diabetes is often preceded by the appearance of insulin autoantibodies and the reports that prophylactic administration of insulin to biobreeding diabetes-prone (BB-DP) rats, nonobese diabetic (NOD) mice, and human subjects results in protection from diabetes suggest that an immune response to insulin is involved in the process of beta cell destruction. We have recently reported that islet-infiltrating cells isolated from NOD mice are enriched for insulin-specific T cells, tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
243
3
5

Year Published

1997
1997
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 397 publications
(257 citation statements)
references
References 30 publications
5
243
3
5
Order By: Relevance
“…In the case of chromatin, Datta et al have shown that a brief therapy of 3-month-old prenephritic SNF1 mice with peptide 16±39 from histone H4 (a peptide that contains a Th epitope recognized by CD4 1 T cells from SNF1 mice) had a tolerogenic effect on autoimmune T and B cells, and markedly delayed the onset of severe lupus nephritis [68]. Other examples have been described in EAE and type I diabetes [69,70]. These results are of considerable interest because it was not expected that a single peptide could control the diversified autoimmune response observed in such diseases.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of chromatin, Datta et al have shown that a brief therapy of 3-month-old prenephritic SNF1 mice with peptide 16±39 from histone H4 (a peptide that contains a Th epitope recognized by CD4 1 T cells from SNF1 mice) had a tolerogenic effect on autoimmune T and B cells, and markedly delayed the onset of severe lupus nephritis [68]. Other examples have been described in EAE and type I diabetes [69,70]. These results are of considerable interest because it was not expected that a single peptide could control the diversified autoimmune response observed in such diseases.…”
Section: Resultsmentioning
confidence: 99%
“…In Type I diabetes, GAD and insulin have been identified as major autoantigens and tolerisation against these autoantigens has been attempted as a method for the prevention of the disease [14,32]. It has been reported that administration of purified GAD protein or peptide or insulin protein or peptide to NOD mice by a variety of routes can tolerise the T cell-mediated immune response against pancreatic beta cells, resulting in the prevention or delay of the development of insulitis and diabetes [28,29,33,34,35,36,37,38,39]. In many cases, the preventive effect was found to be associated with a Th2 shift [14,32].…”
Section: Discussionmentioning
confidence: 99%
“…In NOD mice, several peptides from these autoantigens have been identified as targets of T cell responses. These include GAD65 p524-543 and p246-266 [1, 2], GAD65 p206-220 and p286-300 [3], insulin B chain p9-23 [4,5], proinsulin p24-33 (proinsulin II p48-57) [6],, and insulin-specific glucose-6-phosphatase catalytic subunit-related protein (IGRP) p206-214 [8]. Extensive analysis of TCR BV gene usage and CDR3 sequences have demonstrated that the early islet-infiltrating T cell clonal expansion is restricted to distinct BV families, e.g., BV4 [9], BV2, BV12, BV14 [10], BV13 [11], BV8.2 [12], and BV1 [13].…”
mentioning
confidence: 99%